Charging time and energy storage rate analysis of fin effect inside the horizontal tube for thermal energy storage. (10th November 2020) - Dai, Renkun; Mostaghimi, Javad; Li, Nianqi; Deng, Tianrui; Wang, Qiuwang; Zeng, Min
Abstract: Clean energy storage is of vital importance for cleaner production and environmental protection. This present study focuses on the promotion of clean energy storage efficiency in the widely used shell and tube latent heat thermal energy storage unit. The enhancing effects of fin inside the tube on the charging time and energy storage rate are studied. Numerical investigations are performed through the enthalpy based lattice Boltzmann method couple with curved boundary. Three kinds of configurations for one-fin and two-fin are investigated. Results indicated that fin position can effectively impact the enhancing effects. For one-fin, the maximum difference of the enhanced ratio for different fin positions is 15.17% when R a = 10 7, while it is 7.52% for two-fin. The optimal fin position varies with different Ra, but with appropriate approximation, it can be concluded that one-fin on the bottom and two-fin on the vertical direction are the optimal fin position for one-fin and two-fin cases. In addition, one long fin shows better enhancing effects than two short fins. Under the same fin length, the average enhanced ratio for one long fin is 41.82%, while it is only 27.03% for two short fins. These results can provide guidance for the fin configuration in the shell and tube latent heat thermal energy storage unit to achieve higher energy storage efficiency. Since this unit is widely used in various clean energy storage systems, the results would also be beneficial for various industrial applications of clean energy storage and utilization. Highlights: The characteristics of energy storage process with fins inside tube are obtained. The different enhancing effects caused by fin position can be as high as 15.17%. One-fin on bottom and two-fin on vertical direction are the optimal fin position. The average enhanced ratio for one long fin is 14.79% higher than two short fins. The charging efficiency can be enhanced by 40% with proper fin configuration.